E. Grassi, “La filosofía del Humanismo. Preeminencia de la palabra (Barcelona, 1993) [pp. 423-424]. - Damiani, Alberto M. (Cuadernos sobre Vico, 2020)
CUADERNOS SOBRE VICO, 7-8 (1997). 495 págs. ISBN 1130-7498